Poly(ionic liquid)-derived nanoporous carbon analyzed by combination of gas physisorption and small-angle neutron scattering. (February 2015) - Mascotto, Simone; Kuzmicz, Danuta; Wallacher, Dirk; Siebenbürger, Miriam; Clemens, Daniel; Risse, Sebastian; Yuan, Jiayin; Antonietti, Markus; Ballauff, Matthias
Abstract: The preparation of nanoporous carbon materials and their characterization combining small-angle neutron scattering (SANS) with gas physisorption is presented. Carbon with a porous structure and tunable form is obtained here by a salt-templating approach using poly(ionic liquid) as precursor. SANS in combination with contrast matching by deuterated p -xylene was used for a separation of the scattering component deriving from the density fluctuations of the carbon matrix and the inaccessible porosity. The resulting scattering curves could be used for an unambiguous characterization of the pore structure of the materials. SANS curves measured at different partial pressure of the matching agent p -xylene were used for a differential filling of the micro- and mesopores. The analysis using the chord length distribution (CLD) was employed to determine the specific surface area and the pore size at different adsorption steps. The SANS results were in good agreement with the quenched solid density functional theory (QSDFT) analysis of the nitrogen physisorption. By the comparison of both characterization methods the pore shape could be determined. The combination of both SANS and gas physisorption is thus shown to provide a comprehensive characterization of the pore structure of the carbon monoliths throughout the entire pertinent length scale.